Implementing a Video Project for Assessing Students’ Speaking Skills: A Case Study in a Non-English Department Context - Titik Ismailia; Suyik Binarkaheni (Politeknik Negeri Jember, 2022)
Speaking is one of the productive skills in English. Among the four language skills, speaking tends to be the language skill that seems to be difficult for students to do because it requires students to be able to communicate orally in English. This constraint has led to several studies about the teaching and learning of speaking. To enrich the studies about the teaching of speaking, this paper aims to describe the process of doing a video project by fulfilling all elements of speaking such as grammar, vocabulary, comprehension, fluency, and pronunciation. The participants of the study are 71 students of the Food Crop Production Program at Politeknik Negeri Jember. By doing the project, students can conduct a series of activities as follows: deciding a topic, working on language aspects, planning the video, drafting, editing, uploading the finished video on the YouTube channel, and giving a score of the video. The results show that by conducting the project, the students learn to write a script with better grammar and vocabulary, understand the task, and pronounce English words correctly and fluently. The video project also encourages the students to learn how to edit videos using editing software. This project also helps students and lecturers do collaborative teaching and learning processes to produce a video with some elements of speaking completely.